Chances And Challenges of Strategic Management in The Age of Information Opening - Hartinah, Hartinah; Tamrin, Putri Aulia; Nugroho, Moch. Nur Syawalludin (Institut Agama Islam Negeri Sorong, 2024)
Strategic management is developing, implementing, and evaluating decisions that enable an organization to reach its goals. Furthermore, the study aims to identify the opportunities and challenges of strategic management in the era of information openness. This research uses a library study method by analyzing journals or related articles published in the last five years; as for the research results obtained, the use of SWOT analysis in strategic management to identify opportunities and challenges the organization faces. Following strategic management in the era of information openness, the study of the results of related journals described that organizations exploit information and technology access to perform organizational tasks efficiently. Acquired opportunities and strategic management challenges in the era of information openness include more comprehensive access to data and the ability to access data quickly. Still, the risk of information failure becomes a challenge.